English Reading Comprehension Difficulties Of Ujian Tulis Berbasis Komputer (UTBK) By Senior High School at SMAS Pangeran Antasari Medan - Fachri Yunanda; Bambang Nur Alamsyah Lubis; Azizah Husda; Elsa KristiNancy Br Ginting; Safitri Br. Manalu (Linguistic, English Education and Art (LEEA) Journal, 2022)
The purpose of this study was to determine the challenges that seniors in high school encountered when responding to reading comprehension questions on the UTBK exam. This study employed a qualitative methodology. Senior high school students who have taken the UTBK test were the subjects of this study. This research was conducted in SMAS Pangeran Antasari Medan, in class XII IPA, there are 32 students in it. According to the study's findings, high school students' lack of interest in reading made them bored when reading the text in front of them. It was also difficult for them to decipher the meaning of the text because they lacked the necessary vocabulary and didn't practice answering questions about reading comprehension. As a result, they believed that the UTBK test was too difficult for them. So this research, senior high school students must increase their practice of reading comprehension questions both at home and in class, as well as their interest in reading and vocabulary, to overcome these challenges. This will make it simpler for them to solve problems in the reading comprehension section. Keywords: reading comprehension, UTBK